The role of ALIVP model in developing pesantren students’ argumentation abilities on temperature and heat concepts - Agus Budiyono; Arin Wildani; Akhmad Jufriadi; Luh Sukariasih (Momentum: Physics Education Journal, 2025)
Argumentation abilities are critical for students to develop in physics learning, yet most studies focus on students outside pesantren. This research investigates the argumentation abilities of pesantren students on the topics of temperature and heat. The study employs a pre-experimental design with a one-group pretest-posttest approach. The instrument used is a test comprising six essay questions assessing argumentation abilities. The data in this study were examined using a paired sample t-test, effect size calculation, and N-gain analysis to assess changes in students' argumentation abilities. The findings demonstrated a significant enhancement in students' argumentation abilities following the implementation of the ALIVP learning model. The effect size analysis indicated a very large impact, while the N-gain results classified the improvement as high. A detailed examination of argumentation indicators revealed that the highest increase occurred in claim accuracy, followed by the completeness and credibility of data, strength of backing, and strength of evidence. These findings suggest that the ALIVP model successfully enhances the argumentation abilities of pesantren students in physics learning, bridging a gap in current research. This study underscores the potential of integrating argumentation-focused learning models in pesantren to foster critical thinking in scientific contexts.